Sustainable marketing innovation and consumption: Evidence from cold chain food online retail. (15th March 2022) - Su, Miao; Fang, Mingjie; Kim, Junseung; Park, Keun-sik
Abstract: As reports on the gap between consumer awareness and behaviors in sustainable consumption increase, the effects of sustainable marketing innovation services on alleviating this gap are attracting more and more attention. This study integrates innovation diffusion theory, perceived value theory, and planned behavior theory to study the impact of online retail food cold chain recyclable express package marketing innovation. Specifically, it explores the antecedents, consequences, and mediating factors of sustainable marketing innovation in guiding consumers to participate in express packaging recycling. Survey data were obtained from 581 individuals in the area of Seoul, South Korea, and they were analyzed using structural equation modeling. This study found that the five innovation diffusion characteristics of sustainable marketing innovation services (comparative advantage, compatibility, complexity, trialability, and observability) each have a significant impact on consumers' participation in express packaging recycling. In addition, consumer's perceived value and satisfaction are effective mediators for promoting consumers' participation in express package recycling. This study enriches the literature on enterprise sustainable marketing innovation services using a theory-driven approach and provides practical insights into the effectiveness of using a marketing innovation service to achieve cleaner production for enterprises. Highlights: The determinants of sustainable marketing innovations to promote sustainable consumption are examined. Innovation diffusion theory, perceived value theory, and planned behavior theory are used. Consumer perceived value and satisfaction are effective regulating factors for promoting sustainable consumption. A unique perspective for realizing a sustainable cold chain food online retail consumption ecosystem is provided.